A Model for Near-Field Blast Vibration Based on Signal Broadening and Amplitude Attenuation - D S. Scovira (The Australasian Institute of Mining and Metallurgy, 2007)
The effect of blast vibration on highwall stability is a common concern for many open pit mines. Vibration in such a case is a typical near-field blast vibration situation. Vibration modelling in the near-field of a blast requires consideration of both the amplitude and frequency attenuation of waveforms with distance. Most existing blast vibration models are designed for far-field vibration and do not simulate the frequency attenuation and its effect on waveform shape. With the advent of electronic detonators it is desirable to quantify the effects of blast delay on the amplitude as well as the frequency of blast vibrations. A suitable modelling tool is proposed here. At present, a blast vibration model with double attenuations(amplitude and frequency) has been developed at Orica. The present model simulates the amplitude and frequency attenuations separately using different transfer functions. The amplitude attenuation is modelled according to the non-linear relation between the peak particle velocity (PPV) and the charge weight scaled distance established from the signature hole vibration. The frequency attenuation is modelled with the signal broadening based on KjartanssonÆs transfer function û a linear model for attenuation of waves. The model is capable of taking multiple sets of signature waveforms as input to improve the modelling accuracy of the wave propagation in the geology at a site. The screening effect of the earlier firing holes in the path of a later firing hole is taken into account on not only the amplitude, but also frequency attenuation. The present blast vibration model is suitable for modelling both near-field and far-field blast vibrations. It yields reasonable agreement with measured field data for the near-field vibration examples discussed.